STUDY OF THE ANTIOXIDANT PROTECTION SYSTEM OF RED GRAPESS AND WINE - Irgasheva Gulmira Rakhimjanovna; Sapaeva Zamira Shavkatovna (International Journal of Innovations in Engineering Research and Technology, 2021)
Currently, demand for light red wines has risen sharply. But the color of the wine loses its color and luster during technological treatments associated with the presence of oxygen. Therefore, the study of antioxidants, antioxidant protection system in the processing of red grapes and processing of wines in order to ensure the quality and presentation of red wines is relevant. The work investigated the system of antioxidant protection (AOD) of products of primary and secondary winemaking. Describes the results of research on the determination of enzymes of the AOD system during all technological methods: crushing, dripping, sludge, fermentation, pasting, sludge, heat treatment, cold red wine and wine processing. Before and after each technological operation, the physicochemical parameters, the activity of the enzymes in the AOD system were determined, a cascade of oxygen reduction reactions and oxygen reduction reactions in wine are given.As a result, on the basis of the obtained results, the technological canons of winemaking were corrected, for example, during the processing of red grapes, additional measures are clearly needed to provide antioxidant protection. Moreover, cold treatment of dry red wines leads to an increase in oxygen concentration, which threatens to oxidize the phenol - coloring matter in wine and causes a change in color and taste of wine, then this technological method for red wines is recommended in exceptional cases. Consequently, the treatment with heat of red wines provides an increase in the concentration of oxygen and at the same time activates all the component systems of AOD, there is a dismutation and the formation of organic peroxides. Over time, heat treatment enhances AOA, with that, AOA increases more intensively during heat treatment, slightly lower than AOA during technological processing with cold.